MyPiS.pl jako narzędzie marketingu politycznego. Przyczyny niepowodzenia i upadku serwisu. - Jabłońska, Monika (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
The article is the result of a case study analysis of MyPiS.pl social networking portal created in 2010. It indicates the reasons of running by representatives of the Law and Justice's own social media channel, in the era of so dynamic development of social networking portals like Facebook, Twitter or Our Class. It explains the idea that accompanied the creation of MyPiS.pl, and the result of its transformation within the first months of working. And finally, it pays attention to the mechanisms that worked to the disadvantage of the portal and led to it’s collapse. In order to create the article the method of analysis the archival content available in Internet resources was used.